RELEVANSI NILAI KARAKTER DALAM KITAB TA’LIM MUTA’ALIM DENGAN PROFIL PELAJAR RAHMATAL LIL ‘ALAMIN DI MADRASAH IBTIDAIYAH - Fathan Miftah Shururi; Ani Siti Anisah; Iis Komariah (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2025)
Character education is a crucial aspect in shaping young generations with noble morals to face the challenges of globalization and technological advancements. Ta’lim al-Muta’allim, a book by Sheikh Burhanuddin Al-Zarnuji, presents personal values that can be applied in Islamic education, particularly in shaping the personality of knowledge seekers as a blessing for the universe. This study aims to determine the extent to which the values in student education align with the character of students who exhibit compassion, sympathy, and care for others. The method used is a systematic literature review (SLR) with stages including formulating research questions, searching, selecting, analyzing, and interpreting literature. The results show that student education emphasizes values such as honesty, responsibility, discipline, and respect for knowledge and teachers. These values align with the Rahmatan lil ‘Alamin Student Profile, which is based on tolerance, commitment to goodness, and social care. This study contributes to formulating strategies for implementing moral values in the Islamic education curriculum to produce students who are not only academically excellent but also possess noble character and can make a positive contribution to society